Proyecto a Jugar, a Crear y a Actuar –Haciendo Teatro en Casa- (2021)
This work is based on the experience of creating a didactic material as a blog, designed to bring Bogota children closer to theater through theoretical and practical activities that they can access from their homes, using a device with internet as a computer, tablet or cell phone. A dynamic of self-management by minors is proposed so that they navigate the website according to their particular tastes and interests. independently, or they are invited to include in the proposed activities the participation of other family members, friends, neighbors or close people to make the experiences more enriching and meaningful for the children.